Reaksi Pasar Modal dalam Pilpres 2019 - Titi Rahayu (Universitas Katolik Indonesia Atma Jaya, 2020)
This study aims to provide empirical evidence on the events of the KPU's official announcement whether it has an impact on the reaction of the capital market in Indonesia. The population in this study are companies listed in the IDX80 index. With the purposive sampling method the author obtained a sample of 42 companies, with the criteria not to do corporate action during the observation period. The results show that the market did not react to the KPU's official announcement. For further research, it is expected that it can use different abnormal return calculation methods and use different objects.